2004
DOI: 10.1038/sj.cdd.4401414
|View full text |Cite
|
Sign up to set email alerts
|

The telomeric region is excluded from nucleosomal fragmentation during apoptosis, but the bulk nuclear chromatin is randomly degraded

Abstract: Characteristic steps during cellular apoptosis are the induction of chromatin condensation and subsequent DNA fragmentation, finally leading to the formation of oligomers of nucleosomes. We have examined the kinetics and local distribution of this nucleosomal fragmentation within different genomic regions. For the induction of apoptosis, HL60 cells were treated with the water-soluble camptothecin derivative topotecan (a topoisomerase I inhibitor). The genomic origin of the fragments was analysed by Southern bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…Previous scientific studies have reported that DNA fragmentation is a late event in apoptosis and large fragments are observed in early stages (Schliephacke et al, 2004). The obtained results revealed a strong proapoptotic characteristic feature of p-MCA.…”
Section: Discussionsupporting
confidence: 55%
“…Previous scientific studies have reported that DNA fragmentation is a late event in apoptosis and large fragments are observed in early stages (Schliephacke et al, 2004). The obtained results revealed a strong proapoptotic characteristic feature of p-MCA.…”
Section: Discussionsupporting
confidence: 55%
“…The biological function for telomere aggregation is not yet known. Recent studies, using biochemical approaches, show that telomeric regions are excluded from internucleosomal fragmentation during apoptosis (Schliephacke et al, 2004). Thus, it is possible that, during the onset of apoptosis, telomere aggregation protects these heterochromatic regions from degradation.…”
Section: Discussionmentioning
confidence: 99%
“…16,18,19 Telomere lengths vary significantly between chromosomes, between organs in the body, and between different species. 11,16 For example, average telomere lengths in human cells are 15-20 kb 11,13,20 vs 25-150 kb in mouse cells; and with the lengths varying even between different mouse strains. 21,22 Based on the evaluation of telomeres in 43 mammalian species, Gomes et al 23 observed that the lengths are inversely related life span, leading to the hypothesis that shorter telomeres in longer living organisms provide a mechanism to count cell divisions and to utilize replicative aging as a tumor suppression mechanism.…”
Section: Telomere Sequencesmentioning
confidence: 99%